MoCloFlex: A Modular Yet Flexible Cloning System - Klein, Carlo A.; Emde, Leonie; Kuijpers, Aaron; Sobetzko, Patrick (Frontiers in Bioengineering and Biotechnology, 2019)
Tailor-made cloning solutions are gradually replacing classical cloning methods. Current systems make use of libraries with predefined DNA parts that are joined by Golden-Gate reactions. However, these systems still suffer from specific inflexibilities and the lack of inter-compatibility. Here, we present Flexible Modular Cloning (MoCloFlex) which overcomes this inflexibility by introducing a set of linker- and position-vectors allowing free unit arrangement. Our system, therefore, provides a convenient way to design and build custom plasmids, and iterative assembly of large constructs. To support standardization in synthetic biology, MoCloFlex is compatible with the well-established Modular Cloning standard. Here, we test MoCloFlex form various applications with up to 12 fragments in a single restriction-ligation reaction.